Exploring privilege through feminist gender training. Issue 1 (22nd February 2019) - Ferguson, Lucy
Abstract : Drawing together a number of unaddressed concerns from a range of literatures, this article explores ways of working on privilege in gender training. It calls for feminist gender training that is reflexive, focused on process and grounded in the transformative potential of gender-training moments and encounters. Drawing on black feminist thought and privilege studies, the article engages with the challenges of working on privilege, using feminist pedagogical principles and examples from practice to guide the discussion. New and innovative ways of 'doing' feminist gender training are proposed in the spirit of summoning our 'transformative courage' to collaboratively construct a feminist gender training that explicitly engages with privilege in order to facilitate tangible, lasting transformation for gender equality.